Keamanan dan Perlindungan Hukum bagi Investor Saham di Indonesia - Yohanes Sabbat Satriyawan; Firstnandiar Glica Aini Suniaprily; Suharno Suharno (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
The Concern for investor safety is a major issue in the capital market, including the Indonesian market. With the potential for fraud and other abuse, investors need to have confidence that their investment is safe and protected by a strong legal framework. This study has the objective of analyzing how constitutional law can be used to ensure security and protection for stock investors in Indonesia and proposing the necessary reforms where appropriate. So that an understanding of constitutional law from an investor's point of view can be enhanced to navigate the complex legal landscape surrounding securities trading. The research method used is a normative juridical approach, by highlighting legislation in the realm of constitutional law protecting stock investors. This article review can provide investors with the knowledge and resources necessary to navigate the legal landscape surrounding their investment, help increase investor confidence, protect against fraud and other abuses, and promote strong and stable capital markets. With the right legal protections, investors can make informed decisions about their investments and take advantage of the many opportunities offered by Indonesia's growing economy.